2010
DOI: 10.1007/s11156-010-0173-4
|View full text |Cite
|
Sign up to set email alerts
|

Earnings versus capital ratios management: role of bank types and SFAS 114

Abstract: Banks, Earnings management, Capital management, Bank size, Bank risk, C21, G21, G28, M41, M48,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
28
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
7
28
0
3
Order By: Relevance
“…DeFond and Park, 1997;Leuz et al, 2003) as well as financial firms (e.g. Anandarajan et al, 2003;Anandarajan et al, 2007;Alali and Jaggi, 2011). Among others, Lobo and Yang (2001), Kanagaretnam et al (2003) and Hasan and Wall (2004) reveal that managers of US banks save earnings for future periods by increasing loan loss provisions (LLP) in good times and borrow earnings from the future by releasing LLP in bad times.…”
Section: Introductionmentioning
confidence: 99%
“…DeFond and Park, 1997;Leuz et al, 2003) as well as financial firms (e.g. Anandarajan et al, 2003;Anandarajan et al, 2007;Alali and Jaggi, 2011). Among others, Lobo and Yang (2001), Kanagaretnam et al (2003) and Hasan and Wall (2004) reveal that managers of US banks save earnings for future periods by increasing loan loss provisions (LLP) in good times and borrow earnings from the future by releasing LLP in bad times.…”
Section: Introductionmentioning
confidence: 99%
“…Adding to the literature in a fourth way, we exploit the vast dominance of non-listed banks in the German banking market and thus enhance understanding of earnings management incentives in not publicly-held firms (Beatty et al (2002)). Finally, we join Alali and Jaggi (2010) 3 by being among the first to provide evidence on changes in earnings management behavior of banks brought about by the turmoil of the recent financial crisis.…”
mentioning
confidence: 99%
“…For banks close to the limit, a release decision may primarily be driven by the aim of retaining managerial freedom of decision-making with respect to 340f reserves in the future. LNTA i,t is the natural logarithm of total assets of bank i at the end of year t. This variable is included since it is used as a control in many earnings management studies, and partly found to be significant (Alali and Jaggi (2010)). Finally, we add CRGDP t , which is the aggregate volume of bank lending…”
mentioning
confidence: 99%
“…Since Wall and Koch (2000), emerging studies have examined several issues in the loan loss provisioning literature including: provisioning behaviour during fluctuating business cycles and crisis periods (Laeven & Majnoni, 2003;El Sood, 2012;Agenor and Zilberman, 2015), how procylical LLPs contribute to systemic risk and financial system instability (Borio, Furfine, & Lowe, 2001, pp. 1e57;Wong, Fong, & Choi, 2011), dynamic provisioning to mitigate LLP procyclicality (Saurina, 2009;Perez et al, 2011), the role of LLP in bank earnings management, regulatory capital management, signalling and tax management (Lobo & Yang, 2001;Kanagaretnam, Lobo, & Yang, 2005;Anandarajan, Hasan, & McCarthy, 2007;Perez, SalasFumas, & Saurina, 2008;Ozili, 2015Ozili, , 2017aAndries, Gallemore, & Jacob, 2017), bank manager's provisioning discretion under different accounting and regulatory regimes (Alali and Jaggi, 2011;Hamadi, Heinen, Linder, & Porumb, 2016;Kilic, Lobo, Ranasinghe, & Sivaramakrishnan, 2012;Leventis, Dimitropoulos, & Anandarajan, 2011;Marton & Runesson, 2017;Ryan & Keeley, 2013;Wezel, Lau, & Columba, 2012), provisioning and competition (Dou, Ryan, & Zou, 2016), provisioning under different auditor type, reputation and specialism (Dahl, 2013;Kanagaretnam, Lim, & Lobo, 2010;Ozili, 2017a), provisioning discretion under strong corporate governance mechanism and institutional controls (Fonseca and Gonzalez, 2008;Bouvatier, Lepetit, & Strobel, 2014;Curcio & Hasan, 2015) and provisioning behaviour in several country, regional and international contexts (Pain, 2003;…”
Section: Introductionmentioning
confidence: 99%